The Horn of Africa since 2018: Continuities, Transformations, and Prospects - Zahorik, J.; Ylönen, A. (2025)
This book takes stock of developments in the Horn of Africa since 2018, a key time of political turbulence marked by revolution, military coups, and civil war as well as alliances, peace deals, reforms, and reconciliation processes. Bringing together a group of experienced and younger scholars from the Horn of Africa and Europe, the book investigates the various multi-layered and intertwined factors and consequences of political developments in Ethiopia, Eritrea, Sudan, South Sudan, Djibouti, and Somalia. The authors investigate the endemic political instability across much of the Horn of Africa, while also reflecting on political continuities and transformations, including attempts at peace- and state-building. They consider the important role of regional organizations and intra- and extra-regional actors in the domestic politics of the states in the Horn of Africa. The book concludes with a section focusing on the prospects for reform and conflict resolution in the context of shifting regional power relations. This book will be an important resource for researchers working on contemporary politics, history, and society in the Horn of Africa.